Zinc Prevents Sickness Behavior Induced by Lipopolysaccharides after a Stress Challenge in Rats - Kirsten, Thiago B. [UNESP]; Galvao, Marcella C.; Reis-Silva, Thiago M.; Queiroz-Hazarbassanov, Nicolle; Bernardi, Maria M. [UNESP] (Public Library Science, 2015)
Sickness behavior is considered part of the specific beneficial adaptive behavioral and neuroimmune changes that occur in individuals in response to infectious/inflammatory processes. However, in dangerous and stressful situations, sickness behavior should be momentarily abrogated to prioritize survival behaviors, such as fight or flight. Taking this assumption into account, we experimentally induced sickness behavior in rats using lipopolysaccharides (LPS), an endotoxin that mimics infection by gram-negative bacteria, and then exposed these rats to a restraint stress challenge. Zinc has been shown to play a regulatory role in the immune and nervous systems. Therefore, the objective of this study was to examine the effects of zinc treatment on the sickness response of stress-challenged rats. We evaluated 22-kHz ultrasonic vocalizations, open-field behavior, tumor necrosis factor a (TNF-alpha), corticosterone, and brain-derived neurotrophic factor (BDNF) plasma levels. LPS administration induced sickness behavior in rats compared to controls, i.e., decreases in the distance traveled, average velocity, rearing frequency, self-grooming, and number of vocalizations, as well as an increase in the plasma levels of TNF-alpha, compared with controls after a stressor challenge. LPS also decreased BDNF expression but did not influence anxiety parameters. Zinc treatment was able to prevent sickness behavior in LPS-exposed rats after the stress challenge, restoring exploratory/motor behaviors, communication, and TNF-alpha levels similar to those of the control group. Thus, zinc treatment appears to be beneficial for sick animals when they are facing risky/stressful situations.